Perencanaan Sistem Pengangkutan Sampah Kecamatan Tampan Kota Pekanbaru - Hasmad Setyadi; Jecky Asmura; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Kecamatan Tampan is the largest population District in Kota Pekanbaru with the population in 2017 are 285.932 people. The system of collecting and transporting municipal solid waste in Kecamatan Tampan currently uses indirect system for domestic waste and direct system for non-domestic waste. However, in its implementation, the transport system has not been effective in transporting waste. The result showed that the percentage of waste transported to landfill was 76%. Exceeding the target of Minimum Service Standart (SPM) for municipal solid waste transportation. Designing collection and transportation system using depo transfer increase the frequency of ritation from 14 rites to 23 rites and the addition of 12m 3 armroll container in Pasar Selasa and TPS SMPN 21. Municipal solid waste transportation cost per ton are Rp.45.743. Planned that the service percentage will be 90% at the end of design period. The needs of collection and transportation vehicles at the end of design period are 41 units 3m3 pickup, 7 units 10m3 dump truck 1 unit 12m3 armroll truck and 2 units 30m3 tronton truck.Keywords: Kecamatan Tampan, Transportation system, Ritation, Depo transfer